Cystic lymphangioma in adult: a case report and a review of the literature. Issue 7 (31st July 2020) - Colangeli, Walter; Facchini, Valerio; Kapitonov, Aleksandr; Zappalà, Marta; Bozza, Fabrizio; Becelli, Roberto
Abstract: Cystic lymphangioma (CL) in adult is a very rare pathology. Its etiology remains unclear, but it is supposed to be congenital or to be a result of obstruction and lymph fluid retention of developing lymphatic vessels. It generally occurs in the head and neck region, probably because of the rich lymphatics in this area. It can be easily misdiagnosed with other cervicofacial masses. We present the case of a 56-year-old-female presented with a right-sided painless cervical swelling. Ultrasonography and magnetic resonance imaging were performed and a surgical complete removal was carried out. Histological examination revealed that the mass was composed by a variety of dilated lymph vessels involved in a fibrovascular stroma. Diagnose of CL was done. With this article, we want to highlight the features of CL and its role in the differential diagnoses of adults' cervicofacial masses.